(untitled) (Research, Society and Development, 2024)
Within the spectrum of primary neoplasms of the central nervous system, glioblastoma is the most prevalent, aggressive and lethal subtype, despite therapeutic interventions. In this scenario, target therapy, by developing drugs targeted at specific molecules of the carcinogenic process, emerges as a truly revolutionary option. Therefore, this review aims to map in the literature the target therapies that are or can be used in the treatment of glioblastoma in adults aiming at cancer regression. This is a methodological scoping review study. The databases used were: VHL, PUBMED, EMBASE, SCOPUS and BDTD. In total, 637 studies were identified, of which 31 were selected according to inclusion criteria; In addition, 4 articles were included manually. Upon reading, some drugs, such as apatinib, osimertinib and cetuximab, proved to be effective in the studies carried out, however, they lack applications in larger clinical trials to support their incorporation into standard therapy regimens. Bevacizumab is already established in the treatment of recurrent glioblastoma and/or second- or third-line therapy. Finally, it was concluded that although the treatment and prognosis of patients with glioblastoma still remain unclear today, it is believed and hoped that in a promising future targeted molecular therapy will serve as an ally in the curative treatment for this cancer, as that there is already evidence that some improve quality of life with symptom relief, increase the time free from disease progression and/or patient survival, even for a certain period of time.